The role of neuropathological markers in the interpretation of neuropsychiatric disorders: Focus on fetal and perinatal programming. (16th March 2018) - Fanni, Daniela; Gerosa, Clara; Rais, Monica; Ravarino, Alberto; Van Eyken, Peter; Fanos, Vassilios; Faa, Gavino
Graphical abstract: Senile or neuritic plaques represent the characteristic feature of AD; the amyloid beta 40 peptide together with fragments of neuron terminal process and inflammatory glial cells are the major component. Abstract: The study of neuropathological markers in patients affected by mental/psychiatric disorders is relevant for the comprehension of the pathogenesis and the correlation with the clinical symptomatology. The neuropathology of Alzheimer's disease (AD) recognizes intraneuronal and extracellular neurofibrillary formation responsible for neuronal degeneration. Immunohistochemical studies discovered many interesting results for a better interpretation of the AD pathogenesis, while the "metal hypothesis" supports that metal ions might differentially influence the formation of amyloid aggregates. The most relevant pathological findings reported in schizophrenia originate from computer assisted tomography (CT), Magnetic Resonance Imaging (MRI) studies and Diffusion Tensor Imaging (DTI), suggesting the brain abnormalities involved in the pathophysiology of schizophrenia. The theory of fetal programming illustrates the epigenetic factors that may act during the intrauterine life on brain development, with relevant consequences on the susceptibility to develop AD or schizophrenia later in life. The neuropathological interpretation of AD and schizophrenia shows that the presence of severe neuropathological changes is not always associated with severe cognitive impairment. A better dialogue between psychiatrics and pathologists might help to halt insurgence and progression of neurodegenerative diseases.